TEMPERATURE PATTERNS DURING THE ORGANIC ORGANIC WASTE ORDERS OF NATURAL CHILDREN IN NATURAL ENVIRONMENT AND ARTIFICIAL ENVIRONMENT - H Yulipriyanto (Jurnal Penelitian Saintek, 2005)
The  purposes    of  this   work   are   (I)   to  determine    the  pattern    of temperature    during   the   composting    of   organic   waste   of  chicken manure  at the natural  and artificial  environment   (2)  to determine  the chemical   characteristics   of chicken  manure  Around    700 kg  organic wastes  of chicken  manure put in the hole of land with 2 m length, x2m wide  x lm  height.   The  other  organic   waste  in  same  size  put  in  the artificial   environment.     During  the  composting   we  turn  the  heap  of compost  every  two weeks  especially for  organic  waste  that composted in   artificial    environment.    The   data   we   want   to   collect   is   the temperature   of the heap  of compost  in the exterior  zone   (0-20 em, ), deep zone  (50 cmfrom   surface,)   and   low zone  (80 cm,from   surface). We also  analyse  the  chemical  characteristics   include  the pH,  N,P,K total,  NH4,  Ca .Mg  total  and  c/N  ratio;  while  the   organic fraction analysis  include  the cellulose,  lignin, protein,  total sugar.  The pattern of   temperature   during  composting  present  the thermophilic  phase  in the  beginning   of  composting  for   organic   wastes  of  chicken  manure that  composted   in  artificial   condition.   But  this  thermophilic   phase only    rest  for    one   week     While    natural    environment     give    the thermophilic   phase   longer  until  more  than  4  weeks.  Based   on  this results  we  can  conclude   that  the  rate  of  organic   waste  of  chicken manure     decomposition      during     the     composting      in    artificial environment   is more quick  than that in the   natural  environment.    The chemical  characteristics   of chicken  manure  composted  show  the high contain  of NH4,  but  in the artificial  condition   the  looses  of water  is higher.     Based  on the results  of organic fraction,   the biodegradation of cellulose  and  lignin  in the natural  environment   is significant   than that in the artificial  condition.